"As if Nothing Happened": Experiences of Bereaved Parents in Romania. (September 2020) - Thieleman, Kara; Cacciatore, Joanne
Prior research has found high levels of distress in parents who experience the death of a child; however, Romanian parents, whose experiences are influenced by the nation's shared historical trauma, have not been studied. This mixed-methods study found very high levels of distress in a sample of 237 bereaved parents in Romania, primarily women. Specifically, 89% of respondents scored above the clinical cutoff for trauma responses, 66% did so for anxious responses, and 82% did so for depressive responses. Qualitative analyses of respondents' narratives suggest that, through complex interactions between political, social, and medical systems, the lack of care after the death of a child seems to incite additional distress in parents. These findings warrant further exploration of traumatic grief in Romania, especially in the context of historical and political trauma, and of ways in which support can be provided to grieving parents in this unique cultural milieu.